The Role of Computers in Collaborative E-Learning: Implications for the Future of Digital Education - Didi Kurnaedi (Komunitas Dosen Indonesia, 2025)
The development of digital technology has driven significant changes in the world of education, especially through the implementation of collaborative e-learning. Computers play a crucial role in supporting interactive online learning processes, enabling more effective collaboration between students, educators, and learning resources. This study aims to analyze the role of computers in collaborative e-learning and its implications for the future of digital education. This study uses a descriptive qualitative method, with data collection techniques through literature studies and interviews with educators and e-learning practitioners. The results of the study show that computers function as facilitators in various aspects of collaborative e-learning, such as online-based communication, accessibility of educational resources, and integration of artificial intelligence and big data in learning personalization. The advantages of computers in increasing interaction and effectiveness of learning in the digital environment are the main factors in optimizing collaborative e-learning. However, this study also found several challenges, such as the gap in access to technological devices, the readiness of educators and students to adopt technology, and data security issues in e-learning systems. To overcome these obstacles, continuous innovation is needed in the development of digital infrastructure and increasing technological competence for e-learning users. With the rapid development of technology, it is predicted that computer-based collaborative e-learning will continue to develop into the main learning model in the future. Therefore, this study is expected to be a reference for policymakers and education practitioners in designing more inclusive and effective digital learning strategies.